Neutrophils in oncolytic virus immunotherapy - Zhou, Danya; Zhang, Chenglin; Sun, Jingyi; Yuan, Ming (Frontiers in Immunology, 2024)
Oncolytic viruses have emerged as a highly promising modality for cancer treatment due to their ability to replicate specifically within tumors, carry therapeutic genes, and modulate the immunosuppressive tumor microenvironment through various mechanisms. Additionally, they show potential synergy with immune checkpoint inhibitors. A study report indicates that from 2000 to 2020, 49.5% of oncolytic viruses were administered intratumorally and 35% intravenously during clinical trials. However, both administration methods face significant challenges, particularly with intravenous delivery, which encounters issues such as non-specific tissue uptake, neutralizing antibody responses, and antiviral effects mediated by various immune cells. Despite extensive research into the antiviral roles of CD8+ T cells and NK cells in oncolytic virus therapy, neutrophils—constituting approximately 50% to 70% of human peripheral blood leukocytes—have received relatively little attention. Neutrophils are the most abundant leukocyte subset in peripheral circulation, known for their phagocytic activity. Beyond their traditional roles in bacterial and fungal infections, emerging literature suggests that neutrophils also play a critical role in the body’s antiviral responses. Given the gaps in understanding the role of neutrophils in oncolytic virus therapy, this article reviews current literature on this topic. It aims to provide a theoretical foundation for developing oncolytic virus-based cancer therapies and enhancing their anti-tumor efficacy in future clinical treatments.